Представьте в виде произведения многочленов выражение: 1) ау-3у-4а+12 2) 9а+9-na-n 3) 6x+at+6y+ax 4) 8x-8y+xz-yz 5) mn+m-n-1 6) ab-ac-2b+2c
Представьте в виде произведения многочленов выражение:
1) ау-3у-4а+12
2) 9а+9-na-n
3) 6x+at+6y+ax
4) 8x-8y+xz-yz
5) mn+m-n-1
6) ab-ac-2b+2c
Ответ(ы) на вопрос:
1)y.(a-3) - 4(a-3) = (a-3)(y-4)
2)9.(a+1) -n(a+1)= (a+1)(9-n)
3).? 6(x+y) + a(x+y)=(x+y)(6+a)
4)8(x-y) +z(x-y)=(x-y)(8+z)
5)m(n+1) - (n+1) = (n+1)(m-1)
6) a(b-c) - 2.(b-c)=(b-c)(a-2)
Не нашли ответ?
Похожие вопросы